The mediating effect of affective commitment between organizational justice, job crafting, appreciative leadership and workplace belongingness - Ali, Ghazanfar (2021)
Enterprises globally are facing the issue of work place belongingness whereby, dearth of research exists on how it could be addressed particularly in an emerging private higher education sector in Pakistan. Due to the emerging concept of workplace belongingness, numerous researchers suggest more focus on workplace belongingness in the higher education sector. This study examines the effect of organizational justice, job crafting and appreciative leadership on workplace belongingness. The study also examined the mediating effect of affective commitment between organization justice, job crafting, appreciative leadership and workplace belongingness. The research framework is developed under the norms of belongingness theory. Self-administered questionnaires are distributed to the faculty members in private universities of Punjab and Sindh provinces in Pakistan. A total of 390 questionnaires were used to analyze the data. This study utilizes the partial least squares structural equation modeling (PLS-SEM) to analyze the data. The findings of this study show that the direct effect of appreciative leadership on workplace belongingness is not significant. However, the direct effect of distributional justice on workplace belongingness is significant. Further, the direct effect of interactional justice, procedural justice and job crafting on workplace belongingness is not significant. However, the direct effect of appreciative leadership, distributional, interactional, procedural justice and job crafting on affective commitment is significant. Similarly, the direct effect of affective commitment on workplace belongingness is significant. Further, the mediating effect of affective commitment between appreciative leadership, interactional, procedural justice and job crafting, and workplace belongingness are significant and these are full mediation. The mediating effect of affective commitment between distributional justice and workplace belongingness is not significant. The results show that the mediating effect of affective commitment is significant between organization justice, job crafting and appreciative leadership and workplace belongingness.